Assessment of health risks from heavy metal contamination in breast milk of urban mothers in Malaysia - Ahmad Bustami, Normina; Lee, Yu Zhao; Tan, Chung Keat; Phuna, Zhi Xin; Zaman, Rahela; Ho, Yu Bin; Gaurav, Anand; Tan, Eugenie Sin Sing (BioMed Central, 2025)
Introduction: Breast milk is the essential source of nutrition for infants, yet global studies have increasingly identified the presence of heavy metals in breast milk. Objective: This study aims to quantify the levels of heavy metals in breast milk and assess the associated health risk to infants in Malaysia. Methodology: This cross-sectional study included 106 healthy breastfeeding mothers who completed a questionnaire on maternal exposures, infant risk factors, and socio-demographic data. Breast milk samples (collected 1–3 months postpartum) were analyzed for concentrations of lead (Pb), cadmium (Cd), chromium (Cr), and arsenic (As) levels. Findings: Our findings revealed that 63.2% (n = 67) of the breastmilk samples exceeded WHO’s recommended levels of As; 28.3% (n = 30) exceeded the acceptable limit for Cd; 97.2% (n = 103) exceeded recommended range of Cr; and 40.6% (n = 43) exceeded the recommended range of Pb. Notably, dental amalgam fillings were identified as a potential source of exposure, showing a moderately strong correlation with Cd (r = 0.369, p < 0.01) and Pb (r = 0.439, p < 0.01) levels. Furthermore, caesarean section deliveries were moderately correlated with increased Cd levels in breast milk (r = 0.326, p < 0.05). Approximately 93.4% (n = 99) of the infants had a Hazard Index (HI) above 1, indicating potential non-carcinogenic health risks, with the maximum HI reaching 17.368. Discussion and conclusion: These findings underscore the critical need for further research and intervention strategies to mitigate the risk of heavy metal exposure in infants via breast milk.